Effect of root amputation on the fracture resistance of furcation-involved, intracoronally splinted upper molars - Veronika T. Szabó; Balázs Szabó; Gábor Braunitzer; Balázs Szabó P.; Márk Fráter (Hungarian Dental Association, 2022)
Background: The aim of this study was to evaluate the effect of root amputation on the fracture resistance of furcationinvolved, upper first molar and second premolar tooth units that are intracoronally splinted with fibre-reinforced composite. Materials and methods: 20-20 extracted human upper first molars and second premolars were included in the study. Standard mesio-occluso-distal (MOD) cavities (molars) and standard occluso-distal (OD) cavities (premolars) were prepared. All the molars were root canal treated, and 20 molar-premolar units were created by intracoronal splinting. These units were randomly divided into 2 groups (10-10 in each): in Group 2 the disto-buccal roots of the molars were amputated, while in Group 1 there was no root amputation. Both groups were embedded in metacrylate resin, 6 mm apical from the cemento-enamel junction mimicking furcation involvement. All specimens were submitted to dynamic and static, load-to-fracture tests. Fracture resistance values were recorded and also the fracture pattern was analysed. Results: During the dynamic testing, all the specimens withstood the loads, no specimen fractured. During the loadto- facture test, Group 1 (without root amputation) had significantly higher fracture resistance values (mean = 2184,90 N, n = 10, SD = ±462,133 N), than Group 2 (with DB root amputation; mean = 1752,50 N, n = 10, SD = ±364,932 N; p = 0.032). Conclusions: Root amputation may affect the fracture resistance of furcation-involved, intracoronally splinted upper first molar and second premolar units.